Utilization of The School Mosque as A Center for Fostering Student Religiousity At SMAN 12 Bandung - Al Mubarok, Zulfa Muntaha; Kosasih, Aceng; Abdillah, Hilman Taufiq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
This study explores the utilization of the school mosque as a strategic center for fostering students' religiosity and character development at SMAN 12 Bandung. The research aims to examine the role of the mosque not merely as a place of worship, but as an educational and social space that contributes to students’ moral formation and spiritual growth. A qualitative approach with a case study method was adopted, utilizing interviews, observations, and documentation as the primary data collection techniques. Data were analyzed using descriptive techniques, including data reduction, data display, and conclusion drawing. The findings show that the school mosque plays a multifaceted role in promoting religious habituation through activities such as congregational prayers, Islamic study sessions, Duha prayer programs, mentoring, and community service. These activities enhance students' spiritual awareness, responsibility, discipline, and empathy. The integration of mosque-based programs into the broader school curriculum aligned with the Merdeka Curriculum supports a holistic educational model that balances intellectual and moral development. Furthermore, the study highlights the importance of optimal mosque management involving collaboration among teachers, students, and administrators. The school mosque serves as a culturally embedded space that strengthens students’ identity through faith-based character education. This research contributes to the discourse on faith-integrated education and demonstrates the potential of school mosques to produce not only academically proficient but also spiritually grounded and ethically responsible individuals.